Folic acid deficiency increases brain cell injury via autophagy enhancement after focal cerebral ischemia - Zhao, Yaqian; Huang, Guowei; Chen, Shuang; Gou, Yun; Dong, Zhiping; Zhang, Xumei (The Journal of nutritional biochemistry, 2016)
Folic acid (FA) deficiency is not only associated with an increased risk of ischemic stroke, but also with increased oxidative DNA damage and brain injury after cerebral ischemia–reperfusion. However, the cellular and molecular mechanisms underlying FA deficiency-associated neuropathogenesis are not completely understood. In the present study, we tested the hypothesis that neuronal autophagy in focal cerebral ischemia rats may be involved in the mechanisms of FA deficiency-induced injury to neuronal cells. The results demonstrated that, accompanied by obvious neuron damage, the expression of the autophagic markers LC3 and Beclin-1, and the formation of 8-OHdG (a marker of oxidative stress to DNA) and autophagosomes were significantly increased in the brain cortex after ischemia–reperfusion. FA deficiency further induced neuronal cell death, and significantly increased the formation of autophagosomes and the expression of LC3 and Beclin-1 in NeuN-positive cell bodies after ischemia–reperfusion. The elevated level of 8-OHdG was also observed in the ischemic cortex of FA deficiency-treated animals. Conversely, the neuronal cell injury, autophagosome accumulation and the effects of LC3 and Beclin1 overexpression caused by FA deficiency were partially blocked by an autophagic inhibitor 3-methyladenine. These results suggest that FA deficiency progresses autophagic activation and aggravates the damage in rat brain cortex following focal cerebral ischemia–reperfusion. The oxidative injury may be involved in cell morphological damage and autophagy alteration caused by FA deficiency.